Pengaruh Indeks Pembangunan Manusia (IPM) Terhadap Tingkat Kemiskinan Pada Kabupaten Kawasan Perbatasan Negara Provinsi Kalimantan Barat Tahun 2014-2023 - Purnamasari, Wulan; Muslimin; Sari, Nur Indah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The Human Development Index (HDI) is an important indicator for measuring the quality of life of the community. This research aims to determine and analyze the influence of life expectancy, average years of schooling, and per-capita expenditure on the poverty rate in the border districts of West Kalimantan Province from 2014 to 2023. This research method uses a quantitative approach with a type of library research. The data used consists of secondary data analyzed using panel data regression analysis. The research results show that, partially, life expectancy has a negative and significant effect on the poverty rate with a coefficient value of (-0.998165) and a sig value of (0.0052 < 0.05), the Average Length of Schooling does not have a significant effect on the poverty rate with a coefficient value of (-0.352567) and a sig value of (0.3021 > 0.05), per-capita expenditure does not have a significant effect on the poverty rate with a coefficient value of (0.000352) and a sig value of (0.2539 > 0.05). Simultaneously, Life Expectancy, Average Length of Schooling, and per-capita expenditure significantly affect the poverty rate in the border districts of West Kalimantan Province with a sig value (0.00000 < 0.05).